Much effort, little impact: the politics of public microcredit programs in Malawi - Richard Zidana; Bryson Nkhoma; Victor Kasulo (Cogent Social Sciences, 2024)
This paper contributes to locating the Malawian dynamics into an emerging discourse that argues that current microcredit programs are ineffective because they have become an instrument for serving international and domestic actors’ interests. It aims to analyze key actors’ interests in public microcredit programs in Malawi. Using a qualitative research design, we draw on 16 key informants, representing 13 national actor institutions that hold stakes in the design and implementation of these programs. Thematic analysis of data reveals that politicians are mostly interested in the political patronage function of these microcredit programs. Further, we find that private microcredit players agitate for the disengagement of government in microcredit provision solely to protect their economic interests, while bureaucrats fail to push for technical reforms because they are interested in protecting their jobs by aligning with politicians’ interests. Further, the findings do not support any evidence of donor influence on the configuration of current microcredit programs. Based on these findings, we conclude that the ineffective status quo remains the default mode because it serves the interests of most actors, except private microfinance players. This analysis is critical in shaping the nature and direction of the much-needed reforms as it pinpoints specific key actor institutions that are likely to derail such reforms. The paper recommends an honest political will-driven stakeholder dialogue towards depoliticizing public microcredit programs.